Amino acid supplementation and impact on immune function in the context of exercise - Cruzat, Vinicius; Krause, M.; Newsholme, Philip (BioMed Central Ltd., 2014)
Moderate and chronic bouts of exercise may lead to positive metabolic, molecular, and morphological adaptations, improving health. Although exercise training stimulates the production of reactive oxygen species (ROS), their overall intracellular concentration may not reach damaging levels due to enhancement of antioxidant responses. However, inadequate exercise training (i.e., single bout of high-intensity or excessive exercise) may result in oxidative stress, muscle fatigue and muscle injury. Moreover, during the recovery period, impaired immunity has been reported, for example; excessive-inflammation and compensatory immunosuppression. Nutritional supplements, sometimes referred to as immuno-nutrients, may be required to reduce immunosuppression and excessive inflammation. Herein, we discuss the action and the possible targets of key immuno-nutrients such as L-glutamine, L-arginine, branched chain amino acids (BCAA) and whey protein.